Examination of the Relationship between Mood and Achievement Goal Orientations of the Students Studying at Faculty of Sports Sciences - Erdogan, Barbaros Serdar; Baykose, Nazmi (Asian Journal of Education and Training, 2021)
The aim of this study is to examine the relationship between affect and achievement-goal orientations of sports science faculty students. Participants forming the research group are studying at the faculty of sports sciences at Mehmet Akif Ersoy University, and in terms of gender, the research group consists of a total of 487 students, 272 males and 215 females (x̄age = 23.08 + 3.271). The first of the measurement tools used in line with the research purpose; It is the Achievement Goal Orientations Scale, which was developed by Midgley et al. (1998) and gained literature by adaptation to Turkish culture by Akın (2006) Secondly, the Positive and Negative Affectivity Scale, which was originally developed by Watson, Clarck, and Tellegen (1988) under the name of "Positive and Negative Affectivity Schedule" and adapted to Turkish culture by Gençöz (2000) was used. Pearson Correlation test, Anova test and independent samples t test were used in the solution and interpretation of the data. As a result, it was observed that there was a relationship between the achievement-goal orientations of the sports faculty students and their mood (positive and negative).